Deviace náboženské autority - Štampach, Odilo Ivan (Univerzita Pardubice, 2003)
Unbiased study of religious authority is needed face to face its aberrant exercise in nowdays religious life. In the contemporary Czech environment the idea of a "sect" or "sectarian behaviour" is confused with new religious movemets (NRM) as such. The word "sekta" (sect, cult) has at least four meanings: separated religious community, NRM, authoritarian religious group, destructive cult. It has a derogatory grade. It appears advisable to use this term only for authoritarian communities. This problem ought to be detected and analyzed in both new and old, small and great religious groups. Phenomena of narrow verbal orthodoxy , fundamentaůism and bigotry have something in common with sectarian aberration, but must be correctly diferentiated. Redundance of religious authority is not inscribed in principles of Eastern religions as Hinduism and Buddhism. Only so called "guruism" can be dangerous. Western monotheist prophetic religions emphasize Divine power and human obedience. Religious leaders are deputies of the authority of God himself. Academic religious studies can help educators, advisors, therapists but must not be mistaken for "anti-cultist" or "contra-cultist activities which are often more sectarian (in described sense) than authoritarian "sects" or cults themselves.
Keywords: náboženská hnutí; sekty; RELIGIONISTIKA; autority